The impact of Multiple Mini Interviews on the attrition and academic outcomes of midwifery students. Issue 4 (July 2022) - Sheehan, A.; Thomson, R.; Pierce, H.; Arundell, F.
Abstract: Background: Admission to the Bachelor of Midwifery (BMid) in Australia has traditionally been based on academic ranking. The BMid is a high demand course offered to a limited number of students and therefore choosing applicants who complete the degree is important. Multiple Mini Interviews (MMIs) are used to assess non-cognitive skills and select students into healthcare degrees. One university in Australia has introduced MMIs as part of the application process for the BMid. Aim: Compare attrition rates and Grade Point Average (GPA) scores between students admitted into the BMid using both academic ranking and MMIs, to those admitted on academic ranking alone. Methods: A basic convergent mixed methods design, using an explanatory unidirectional framework to integrate data. Attrition rates, GPA, and multiple mini interview scores (2013–2019), were linked and compared for before and after the use of MMI's. Focus groups with students, interviewers, and hospital-based educators, explored stakeholder experiences. Open-ended questions from an applicant survey were added to the qualitative data set, which was analysed thematically. Findings: Students who enrolled via the MMI's had significantly lower attrition rates than those enrolled before MMI's were introduced. GPA scores were significantly higher for students who enrolled via the MMI's. Integration of data found MMI's identified students passionate to undertake midwifery, and that success at the interviews increased students' confidence to successfully complete their studies. Conclusion: MMI's as part of the entry process into the BMid enabled identification of applicants more likely to remain in the course and succeed in their studies.